2022
DOI: 10.7554/elife.79966
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast-mediated resorption primes the skeleton for successful integration during axolotl limb regeneration

Abstract: Early events during axolotl limb regeneration include an immune response and the formation of a wound epithelium. These events are linked to a clearance of damaged tissue prior to blastema formation and regeneration of the missing structures. Here, we report the resorption of calcified skeletal tissue as an active, cell-driven and highly regulated event. This process, carried out by osteoclasts, is essential for a successful integration of the newly formed skeleton. Indeed, the extent of resorption is directly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…In situ hybridization was used to assess gene expression in sectioned tissues. Probes for the axolotl Kazald2 and Krt17 were generated as previously described (Riquelme-Guzmán et al, 2022). Primer sequences for probe amplification were taken from Leigh et al, 2018( Krt17 ) and Bryant et al, 2017 ( Kazald1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization was used to assess gene expression in sectioned tissues. Probes for the axolotl Kazald2 and Krt17 were generated as previously described (Riquelme-Guzmán et al, 2022). Primer sequences for probe amplification were taken from Leigh et al, 2018( Krt17 ) and Bryant et al, 2017 ( Kazald1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In axolotls, several highly expressed transcripts were identified in perichondrial cells based on the expression of Col8a2 ( Gerber et al, 2018 ). Additionally, lineage tracing using transgenic reporter lines identified that Col1a2 + perichondrial cells contribute to the regenerated structure ( Gerber et al, 2018 ), and that some perichondrial cells express Ctsk upon amputation ( Riquelme-Guzmán et al, 2022a ). Moreover, the expression of PTHrP and Gli1 was reported in the perichondrium of newts ( Kaucka et al, 2022 ).…”
Section: How Are Bones Formed In Salamanders?mentioning
confidence: 99%
“…Tissue histolysis is the clearance of debris and non-functional tissue prior to blastema formation ( Stocum, 2017 ). In the skeleton, a rapid and substantial resorption of the calcified tissue (in both cartilage and bone) occurs starting at 5 days post amputation (dpa) ( Riquelme-Guzmán et al, 2022a ). This resorption is driven by multinucleated Ctsk + /Trap + resorbing cells.…”
Section: How Is the Limb Skeleton Regenerated In Salamanders?mentioning
confidence: 99%
See 2 more Smart Citations